AN ANALYSIS OF FACTORS ASSOCIATED WITH DELAYED DIAGNOSIS AND TREATMENT OF UNDESCENDED TESTIS - Rachmat Setiawan, Ilham; Nurhadi, Pradana; Daryanto, Besut (Indonesian Urological Association, 2025)
Objective: This study aimed to analyze factors contributing to delayed diagnosis and treatment of UDT patients at Saiful Anwar General Hospital in Malang. Material & Methods: This retrospective study was conducted at Saiful Anwar General Hospital focusing on patients who underwent orchiopexy or orchiectomy for UDT between January 2019 to February 2024. Delays in treatment were defined as surgery performed after 18 months of age. Statistical analysis involved a comparative study between delayed and non-delayed cases, with a significance level of p<0.05. Results: This study evaluated 140 patients with UDT, aged 3.7 ± 3.87 years old, with 77.1% experiencing delayed referrals. The most common associated anomaly was hypospadias (29.3%). Factors contributing to delayed referral include undiagnosed UDT, inadequate follow-up, and advice to await spontaneous testicular descent, observed in 62% of delayed cases (p = 0.025). Parental unawareness of the risks associated with delayed surgery and misdiagnosis by healthcare providers were significant contributors, affecting 72% and 74% of delayed cases, respectively (p = 0.032 and p < 0.005). Referral sources differed significantly, with pediatricians accounting for 43% of non-delayed referrals, compared to only 8% for delayed cases. General practitioners were responsible for 70% of delayed referrals, and 22% were self-referred (p < 0.005). Conclusion: Most pediatric patients at Dr. Saiful Anwar General Hospital experienced delayed treatment of UDT, often due to referral delays and undiagnosed conditions. Training for primary health-care providers and routine testicular examinations are essential. Keywords: Delayed factors, diagnosis and treatment, undescended testis.